Analysis of Determinants of Village Administrative Service Quality - Sitti Husna Noviana Djou; Agrista Tueno; Sri Apsin Gaib; Sri Nabila Dulupi; Miranda Darise; Darman Darman (West Science Business and Management, 2023)
By observing 99 samples of the Bunga Village Community, Bone Raya Subdistrict, Bone Bolango Regency, this study attempts to explain the influence of village administrative staff competence and environmental factors on the Quality of Village Administration Services. Data were analyzed using the PLS-SEM technique through SMARTPLS version 3 software. Samples were selected and collected through purposive sampling by setting criteria for people who had received administrative services and distributing them via online questionnaires via the Google form. The results show that the competence of village administration officers has a significant effect, with a T Statistical value of 2.846 and P Values of 0.005 while environmental factors have a significant effect, with a T Statistical value of 2.047 and P Values of 0.041 on the Quality of Village Administration Services.